(untitled) (UNED Research Journal, 2018)
Student self-regulation, previous preparation of tutors and collaborative work are key factors in distance education. We tested a new tutoring design in the Physics for Science Teaching III course of the Distance State University of Costa Rica (UNED). A survey indicated that teachers must focus on student motivation; class environment -which influences student focus; and the fact that tutoring is a good tool for diagnostic and formative evaluation. Performance improved with the new model. We recommend strategies to improve self-assurance and performance in written tests, collaborative work and individual attention